2018
DOI: 10.1016/j.sjbs.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The utility of inflammation and platelet biomarkers in patients with acute coronary syndromes

Abstract: IntroductionThrombotic and inflammatory mechanisms are involved in the pathophysiology of acute coronary syndrome (ACS). The aim of the study was the evaluation of inflammation (white blood cells count/WBC, C-reactive protein/CRP, interleukin-6/IL-6) and platelet (platelet count/PLT, mean platelet volume/MPV, large platelet/LPLT, beta-thromboglobulin/β-TG) biomarkers in the groups of ACS patients depending on the severity of signs and symptoms and compared to controls without coronary artery disease.Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
3
26
0
1
Order By: Relevance
“…Adult studies have shown that high MPV increases thrombosis. 34,35 Studies in adults also showed that increased RDW and RPR are correlated with inflammation. [18][19][20][21]36 The increase in RDW is thought to occur as a result of inflammatory cytokines inhibiting erythrocyte maturation and accelerating the passage of younger and larger reticulocytes into the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies have shown that high MPV increases thrombosis. 34,35 Studies in adults also showed that increased RDW and RPR are correlated with inflammation. [18][19][20][21]36 The increase in RDW is thought to occur as a result of inflammatory cytokines inhibiting erythrocyte maturation and accelerating the passage of younger and larger reticulocytes into the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 expression is shown to be elevated in induced myocardial infarction by transcoronary ablation of septal hypertrophy, suggesting its diagnostic role [75]. Additionally, CRP and IL-6 are both significantly upregulated in acute coronary syndrome [76]. e IL-6 concentration, independent of the already established predictors, is also related to adverse cardiac events [77,78], supporting its potential therapeutic target in unstable ischemic heart disease [78].…”
Section: Interleukin-6 (Il-6)mentioning
confidence: 97%
“…Mean platelet volume (MPV) and beta-thromboglobulin (beta-TG) are two important platelet biomarkers that may increase during platelet activation and have a higher expression in patients with coronary artery diseases [76]. High MPV value also correlates with an increased incidence of long-term adverse events, especially all-cause mortality in NSTEMI patients undergoing PCI [107].…”
Section: Platelet Related Biomarkersmentioning
confidence: 99%
“…WBCs play a crucial role in the progression of atherosclerosis and destabilization and rupture of a plaque, leading to thrombotic events. Previous studies have reported increased admission WBC count to be a robust predictor of morbidity and mortality in patients with acute coronary syndrome (ACS) [ 1 , 2 ]. Platelets play a key role in atherothrombosis leading to ACS, and patients with increased platelet activation are at higher risk of cardiovascular events in the setting of ACS.…”
Section: Introductionmentioning
confidence: 99%